Sustainable Management of Laying Hens: Review of Current Challenges and Future Prospects - Ismiraj, Muhammad Rifqi; Mayasari, Novi; Firmansyah, Indra; Wulansari, Asri (Bulletin of Applied Animal Research, 2024)
Sustainable management of layer poultry is essential for balancing productivity with environmental, economic, and social responsibilities. As demand for eggs continues to rise, the layer poultry industry faces increasing pressure to adopt practices that minimize environmental impact, reduce resource use, and improve animal welfare. Sustainability in layer poultry management not only supports ecological health but also aligns with consumer preferences for ethically produced animal products. This review identifies and discusses the challenges in layer poultry production, evaluates current sustainable practices, and explores innovative approaches that can enhance sustainability. The review aims to provide a comprehensive overview of best practices and future prospects for the industry. Sustainable practices, such as using alternative feed sources, implementing waste-to-resource systems, and adopting welfare-friendly housing, show promise in addressing these challenges. Future prospects include integrating renewable energy, precision farming technology, and enhanced waste management strategies to further support sustainability goals. Sustainable practices are essential for the long-term viability of the layer poultry industry. Holistically addressing environmental, economic, and social factors can create a resilient egg production system that meets both consumer demand and ecosystem needs.